THz Metamaterial Biodetection Platform for Label-Free, Sensitive and Selective DNA-, Protein- or Supermolecular-Based Biomarker Analysis - Richter, Merle; Loth, Yannik; Rachinger, Nicole; Wigger, Anna K.; Boßerhoff, Anja Katrin; Bolívar, Peter Haring (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
This work is dedicated to present a versatile, metamaterial-based sensing platform for biomarker detection in the THz frequency regime. The sensor can be classified as frequency selective surface and exhibits a characteristic dual resonance feature in the transmission frequency response which has been proven to perform well in biosensing applications. The platform is able to selectively detect proteins such as transcription factor EGR2 (early growth response protein 2) from a complex sample matrix with more than 7 · 103 other protein species, to sensitively detect reverse-transcribed MIA (melanoma inhibitory activity) DNA from a complex sample matrix and to respond to extracellular vesicular structures as well.
CRIS-Team Scopus Importer:2024-07-19
Keywords: EGR2; melanoma; metamaterial-based biosensing; metasurface; MIA; sensitivity; specificity; THz spectroscopy